A survey of infective larvae of Gnathostoma in eels sold in Ho Chi Minh City - Le Thi Xuan (2018)
To investigate the distribution of Gnathostoma spp in Ho Chi Minh City (HCM city), 1,081 eels were purchased from a local market twice a month from March 1998 to February 1999. Infective larvae of Gnathostoma spp detected from the flesh and liver of eels by the press preparation technique were examined and identified. Three hundred and fifty advanced third-stage larvae were recovered from liver, none from the flesh. The average rate of infection was 0.11; a high rate of infection was found from August to November and a low rate of infection from February to May. The average number of larvae/eel was 2.9; the greatest number of larvae/eel was in January whereas the lowest was in March and April. There was a marked decrease in both prevalence and intensity of infection from February to May, followed by a rise from June. The finding suggests that in HCM city, the infection rate abruptly decreases soon after the end of the rainy season and starts to rise when the rain comes and reaches its peak at the end of the rainy season. All recovered larvae were identified as G. spinigerum.